Temporal Variation of Biochemical Markers and Adenoma Predictors in Normocalcemic Primary Hyperparathyroidism: A Multicenter Retrospective Analysis - Aycicek, Bercem; Tuna, Mazhar Muslum; Engin, Ismail; Sahin, Mustafa; Zuhur, Sayid; Gulcelik, Nese Ersoz; Basmaci, Nergis (Wiley, 2025)
Objective: This study aimed to evaluate the diagnostic performance of biochemical markers in normocalcemic primary hyperparathyroidism (nPHPT), analyse their temporal variations, and assess their correlation with adenoma localisation and size. Methods: In this multicenter retrospective study-the largest patient cohort reported in the literature to date (n = 474) we comprehensively profiled normocalcemic patients diagnosed with primary hyperparathyroidism nPHPT was diagnosed based on persistently elevated PTH levels with normal serum calcium after excluding secondary causes such as vitamin D deficiency, renal impairment, and other conditions. This retrospective multicenter study included a large cohort of patients whose biochemical markers-including serum calcium, phosphorus, magnesium, vitamin D, parathyroid hormone (PTH), and glomerular filtration rate (GFR)-were measured at three time points, using standardised laboratory protocols. Although in routine clinical practice these measurements are typically performed at regular intervals of 3-6 months, resulting in approximately three assessments during an 18-month follow-up period. Urinary calcium and creatinine levels were also determined, and imaging modalities (ultrasonography, sestamibi scintigraphy, and computed tomography) were employed for adenoma detection. Statistical analyses comprised repeated measures ANOVA, logistic regression, correlation analysis, and ROC analysis, performed using Jamovi software. Results: Serial evaluations revealed significant temporal changes in key biochemical parameters, including a significant decline in serum calcium and PTH levels alongside a significant increase in urinary calcium excretion. Logistic regression analysis identified higher PTH levels, higher corrected calcium, and larger adenoma size as independent predictors of adenoma localisation, while ROC analysis confirmed that PTH exhibited the highest diagnostic accuracy (AUC = 0.91, 95% CI: 0.84-0.95, p < 0.001). Conclusion: The large scale of our patient cohort reinforces the robustness of our statistical analyses and provides comprehensive insight into the dynamic nature of nPHPT.
Keywords: adenoma predictors; biochemical markers; diagnostic performance; imaging modalities; longitudinal analysis; normocalcemic primary hyperparathyroidism; nPHPT